Lessons learned by giving amphetamine to antipsychotic-medicated schizophrenia patients - Swerdlow, Neal R. (Neuropsychopharmacology, 2019)
Experimental Medicine studies in psychiatric populations test specific, mechanistic hypotheses related to the biology of mental illness, by combining well-characterized neurobiological probes and laboratory-based measures of behavioral performance and neurobiology. However, scientific inquiry through the acute administration of psychoactive drugs to patients with serious mental illness raises important ethical issues. These issues arise in studies in which the psychostimulant, amphetamine, is used as an Experimental Medicine probe in patients with schizophrenia. In this study, we summarize relevant aspects of our experience with acute, laboratory-based challenges of amphetamine in schizophrenia patients. Schizophrenia patients participated in one or more Experimental Medicine studies involving limited doses of amphetamine with clinical monitoring, over a 4-year period. Acute (within hours of ingestion; collective n = 53), subacute (three active doses over 4 weeks; n = 28), and long-term (mean = 17 months after ingestion; n = 19) effects of amphetamine ingestion were assessed. In antipsychotic (AP)-medicated schizophrenia patients, amphetamine was associated with no detrimental subjective, autonomic, or functional changes. Symptoms assessed acutely, subacutely, or long term were either unchanged or diminished. No adverse acute, subacute, or long-term consequences from the Experimental Medicine use of amphetamine in antipsychotic-medicated schizophrenia patients were detected. These findings do not address the safety or effectiveness of the use of amphetamine in unmedicated patients, or as an adjunctive treatment for schizophrenia. Indeed, it is important to distinguish evidence-based risks of symptom exacerbation in an Experimental Medicine setting vs. risks associated with long-term, daily clinical use or even misuse of amphetamine.